Surface Functionalization of Gold Nanoparticles for Physical Antibiotics Coping with Antibiotic-Resistant Bacteria - Yujiro Naruse (Journal of Basic & Applied Sciences, 2015)
Surface functionalization of gold nanoparticles is theoretically investigated in order to develop physical antibiotics coping with antibiotic-resistant bacteria. The core concept of the physical antibiotics is based on the design strategy utilizing molecular elements in peptidoglycan for surface functionalization of gold nanoparticles. These gold nanoparticles will couple to peptidoglycan easily during the proliferation or growth of the bacteria, leading to the destruction of cell walls. Additionally, physical fields (electromagnetic wave, X-ray or ultrasound) bring enhanced suppression of the proliferation. This strategy allows us to have wide variety of antibiotics designs and the suppression against the outbreak of antibiotic-resistant bacteria.